ALGORITMA DALAM PRAKTIK PENEMUAN HUKUM MODERN - Aritonang, Rasamala (Veritas et Justitia, 2024)
A defining characteristic of modern society is its reliance on general rules and regulations that derive legitimacy from scientific methods and findings, instead of customs or tradition. These rules are not typically enacted by individuals such as kings or priests with divine or prescriptive authority but are instead guided by rational and impersonal principles developed by "experts." Consequently, the modernization of law has involved leveraging scientific and technological advancements, such as the use of algorithms, to develop and improve legal systems. The evolution of legal systems is closely linked to the lawmaking process, often shaped by various legal professionals, particularly judges. This research explores the application of computational algorithms in the lawmaking process, focusing on their accountability and practical implementation. Additionally, it investigates whether legal decisions produced by algorithms can be rationally accepted as embodying "justice" when applied in judicial verdicts. This study employs a normative legal research methodology with an interdisciplinary doctrinal approach to address these questions.